Pengembangan Program Pendidikan Karakter untuk Meningkatkan Akhlak dan Moral Anak di Era Digital: Penelitian - Komarudin, Komarudin; Lindayati, Eka; Asy’ari, Hasan; Noviani, Dwi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The digital era has brought significant changes to children’s behavior and morality. Unlimited access to information often leads to a decline in the values of character and spirituality among the younger generation. This study aims to develop a character education program relevant to the needs of children in the digital age to enhance their morals and ethics. The research employs a qualitative descriptive approach using literature study and document analysis techniques. Data were obtained from various scientific sources, including journals, books, and recent research reports. The results indicate that character education becomes more effective when integrated with digital technology through contextual approaches, project-based learning, and digital role modeling. Strengthening religious values, responsibility, empathy, and digital ethics serves as the main pillars in developing the program. The findings emphasize the importance of synergy among families, schools, and communities in nurturing morally upright children amid the challenges of the digital world.